The role of long non-coding ribonucleic acid HOXA11-AS in endometriosis therapy - Ramanaiah Mamillapalli; Nimisha Gawde; Madeline Fay; Rula Atwani; Irene Moridi; Hugh S. Taylor (Reproductive Biology and Endocrinology)
Abstract Objective To investigate the function of HOXA11-antisense long non-coding RNA (HOXA11-AS) in endometriosis treatment response. Methods Tissue samples (ectopic and eutopic endometrium) were obtained from surgically diagnosed subjects with endometriosis (n = 15) and controls (n = 11) without endometriosis after treatment with a progestin. RNA was extracted from these tissues; cDNA was prepared and lncRNA HOXA11-AS levels were measured by quantitative real-time polymerase chain reaction (RT-qPCR). Immortalized endometrial stromal cells from an endometriosis patient (ENDO cell line) were cultured and transfected by HOXA11-AS plasmid and potential target genes were analyzed by RT-qPCR. Results Progestin therapy led to lower lncRNA HOXA11-AS expression. HOXA11-AS was most decreased in ectopic endometriotic lesions, lower by 81% compared to eutopic endometrium from women with endometriosis. There was no difference in progestin response between eutopic endometrium in endometriosis and normal endometrium from controls. A HOXA11-AS plasmid was used to increase HOXA11-AS expression in an endometriotic cell line. Increased HOXA11-AS led to a significant increase in the expression of genes ITGB3, AKT1, MMP2, and MMP9, which have a role in cell proliferation and tumorigenesis. HOXA11-AS also upregulated the mRNA levels of tumor suppressor and apoptotic regulatory genes PTEN, BCL2 and Caspase3. Conclusions HOXA11-AS is a critical regulator of normal endometrial development. HOXA11-AS is elevated in endometriosis contributes to its pathophysiology. This long non-coding RNA was decreased in women undergoing endometriosis treatment with progestins. HOXA11-AS regulated several key drivers of disease and repression during treatment likely has a central role in preventing growth and invasion of endometriosis.